Experience in Railway Track Testing for Validation of Theoretical Dynamic Analysis - Moravcik, Milan (Communications - Scientific letters of the University of Zilina, 1999)
The objective of this paper is to present some experimental approaches in dynamic testing of the railway track structure. The load - deflection track characteristics are particularly important in the design, in the evaluation of serviceability of concrete-sleepers tracks, and to improviding data for computer modelling of the track dynamic behaviour and the dynamic vehicle/track interaction analyses. Thus, results of theoretical dynamic analyses of the track structure must be verified and compared with obtained experimental results. The herein presented track testing for validation of dynamic analyses can give many useful indications concerning the evaluation of the superstructure behaviour.